Construction of a Specific Test Battery of Motor Fitness for Medium Pace Bowlers in Cricket: Development of a Test Battery for Motor Fitness in Medium Pace Bowlers (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The study was conducted on selected motor fitness components on 30 male Inter-University level cricketers with the purpose to construct a specific test battery of motor fitness for medium pace bowlers. The selected motor fitness components were Speed, Strength, Agility Endurance and Flexibility. Construction of a specific test battery of motor fitness for medium pace bowlers in cricket asses the relationship of criterion with each of test item further wherry do little method of multiple correlation was computed to find out the combined contribution of all the test items. The multiple regression equations were worked out to assess the relative contribution of different selected test item to specific motor fitness of medium pace bowlers. On the basis of results, the following conclusion were drawn The multiple correlation fielded eight specific motor fitness tests, namely, Push-ups (5), Vertical jump (8), Leg raising just one feet above the ground (11), W.M. Agility (14), Six point run (16), Dips on parallel Bar (18), Trunk flexion (22), identified to be meaningful in representing the specific motor fitness of medium pace bowlers. All the eight tests showed high significant relationship with the bowling playing ability. The battery of tests developed by the researcher has the ability to predict the specific motor fitness of medium pace bowler.